Suku Duo Piak: Representation of Solidarity in the Wedding Feast Tradition in the Village of Semerah - Fitri, Ayura Rahmadhani; Zufriani, Zufriani; Iskandar, Nuzul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
In the midst of the development of the times, the tradition of mutual cooperation in wedding ceremonies is still a bond of togetherness in rural communities. This study examines the tradition of walimah in Semerah Village, which not only involves cooperation between residents, but also the practice of recording and returning donations as a way to maintain social relations. The purpose of this study is to understand how this tradition strengthens the sense of togetherness or solidarity between residents. This study uses a qualitative approach with observation, interviews, and documentation as data collection techniques. The analysis was carried out descriptively to reveal the social meaning in each stage of the event. The results of the study show that mutual cooperation and the donation system in this tradition are not only about helping, but also a way to maintain balance and strengthen relations between residents. Recording donations serves as a reminder of relationships and a form of shared social responsibility. Traditions like this are important to maintain because they are a real example of how the value of togetherness remains alive even though the times continue to change.